The Reclamation of Tailing Area Reclamation in The Mining Area with Forages, is it Possible? - N D Purwantari (Indonesian Center for Animal Research and Development, 2007)
Tailings are what’s left over from mining. The rock where copper, gold, silver and other minerals found is ground up into fine particles so that the valuable material can be taken out and refined. The solid waste would affect the environment physically and biologically. Characteristics of tailing are high porosity with low water holding capacity, poor organic matter, poor macro and micro nutrients and no microorganism activity. Therefore, it takes time and requires strategy to manage and change them to a more productive area. Many technologies have been applied to rehabilitate tailing for agriculture. The technologies including the use of manure, compost, mulch, biosolid, chemical fertilizer, microorganism (bacteria, mycorhiza) and phytoremediation. Phytoremediation is the use of plants to remediate selected contaminants in the contaminated soil, sludge, sediment, water (ground, surface, waste water). Phytoremediation encompasses a number of different methods that can lead to contaminant degradation, removal or immobilization. Those methods including phytodegradation/rhizodegradation, phytoextraction, phytovolatilization and phytostabilization. The phytoextraction is inexpensive compared with the conventional technology. Some forages have been used for phytoremediation such as Paspalum notatum (Bahia grass), Vetiveria zizonoides (Vetiver grass), Cynodon dactylon (Bermuda grass), since they have been known as heavy metal hyperaccumulator plant. Key words: Tailing, reclamation, forage, phytoremediation